2009
DOI: 10.1111/j.1463-1318.2009.02150.x
|View full text |Cite
|
Sign up to set email alerts
|

Strict follow‐up programme including CT and 18F‐FDG‐PET after curative surgery for colorectal cancer

Abstract: A total of 72% of recurrences were detected at scheduled controls. The findings supported a strict follow-up program following curative surgery for colorectal cancer. FDG-PET combined with CT should be included in control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A recent prospective, non-randomized study demonstrated that the majority of patients with recurrent CRC were identified at scheduled visits in a strict follow-up program. In that trial, CT and FDG-PET combined had better diagnostic properties than other imaging modalities [ 12 ]. A very recent randomized trial with more than 1,200 patients showed no benefit of combining serial CEA measurements with CT versus CT or CEA alone [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective, non-randomized study demonstrated that the majority of patients with recurrent CRC were identified at scheduled visits in a strict follow-up program. In that trial, CT and FDG-PET combined had better diagnostic properties than other imaging modalities [ 12 ]. A very recent randomized trial with more than 1,200 patients showed no benefit of combining serial CEA measurements with CT versus CT or CEA alone [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the first CT scan ranging from 3 to 12 months after curative resection. However, accumulated incidence of recurrence within 6 months detected by CT scan and the relevant value were not reported .…”
Section: Discussionmentioning
confidence: 99%
“…We did not collect data for this systematically, but several larger hospitals reported the use of this in their 'free text' responses. Better imaging alternatives are attractive in this setting [19], but not widely available and still costly. Despite the relative paucity of evidence of efficacy, more frequent and liberal use of imaging is now implemented in the current surveillance programme [11].…”
Section: Discussionmentioning
confidence: 99%